Implementation of MENTARI (Mental Health Remaja Indonesia) Application Innovation Assessment for Early Detection of Adolescent Mental Health at SMPN 1 Purwadadi - Reni Hertini; Tita Rohita; Daniel A. Wibowo (Pengabdian: Jurnal Abdimas, 2024)
Background. Indonesia is one of the developing countries with a significant number of mental health patients. The prevalence of emotional disorders with symptoms of depression and anxiety among the population continues to increase, leading to a rising tendency for self-harm and suicide. Suicide cases in Indonesia can reach up to 10,000 or equivalent to one suicide case every hour. Purpose. The aim of this community service is to provide early detection for adolescents by introducing an application named MENTARI (Indonesian Adolescent Mental Health) Assessment. Method. The implementation is carried out by guiding students to download the MENTARI Assessment application available on the Playstore. Users will directly know their results whether they are normal, borderline, or below the threshold (abnormal). Results. Based on the results of the implementation of the MENTARI application innovation, it can be concluded that the majority of the emotional category is below the threshold, the majority of the behavior category is below the threshold, the majority of the hyperactivity category has normal results, the peer category has normal results, and the prosocial category also has normal results. For the difficulty level in grade 7, there is a difficulty level of 62.5%, grade 8 has a difficulty level of 8.02%, and for grade 9, the difficulty level is 6.41%. Conclusion. Adolescence is a period filled with changes and challenges, both physically, emotionally, and socially. Challenges such as puberty, changes in social roles, and adaptation to the environment can lead to pressure and stress. If unable to cope with these challenges, adolescents are at risk of experiencing emotional problems and significant stress in their lives. Therefore, early detection through applications like MENTARI is crucial to provide appropriate interventions and support adolescents in facing these challenges.